Spinal arachnoid webs in adults: Clinical and imaging features in a multicenter study. Issue 2 (20th January 2023) - Elkadi, Seleem; Kraus, Amanda; Krisanda, Emily; Sayah, Anousheh
Abstract: Background and Purpose: Spinal arachnoid webs (SAWs) are rare and can present with myelopathic symptoms. This study aims to add 85 more cases of SAWs to the literature so we can continue to analyze clinical and imaging trends of SAWs to better understand this entity and its natural history. Methods: An institutional review board‐approved retrospective review of SAW cases between 2016 and 2022 within a metropolitan, multihospital network was performed, searching for MR and CT reports that included "arachnoid web." Of 108 identified reports, 85 patients had imaging and/or pathologically proven arachnoid webs. Demographic and clinical data were collected. Images were analyzed for SAW level, point of maximum kyphosis, presence of cord expansion, and signal intensity. The electronic medical record (EMR) was reviewed for age, sex, symptom presentation and duration, management, and outcomes. Results: Of 85 cases, the most common presenting chief complaint was back pain and weakness. All (100%) SAWs were in the dorsal thoracic subarachnoid space, with 87% (74/85) located from thoracic (T) 2 to T6. Spinal cord expansion and signal abnormality were present in 54.1% and 23.5%, respectively. Twenty‐six underwent surgical resection with 20 showing improvement of at least one symptom. Conclusion: We present 85 additional cases of SAWs to the existing literature. Our cases all occurred in the dorsal thoracic subarachnoid space, predominantly from T2 to T6. Patients present with symptoms like other causes of cord compression, and spinal MR studies should be evaluated routinely for the findings of SAWs. Further research could focus on understanding SAW prevalence, risk factors, and pathophysiology.